Key parameters of measles virus production for oncolytic virotherapy - Weiss, K.; Salzig, D.; Mühlebach, M. D.; Cichutek, K.; Pörtner, R.; Czermak, Peter (My University, 2012)
Attenuated measles virus has revealed selective tumor cell killing and is currently tested in clinical trials for the therapy of cancer patients. The amount of infectious particles per dose needed for oncolytic therapy can be more than a million times higher compared to vaccination. This requires highly effective production processes which guarantee the measles virus quantities needed for its use in cancer therapy. Referring to measles virus production itself, several factors are influencing process parameters and subsequent virus yields. These factors are medium optimization, feeding of nutrients, an optimal multiplicity of infection, localization of produced virus particles, temperature sensitivity and time of harvest. This review summarizes the available data concerning measles virus production in cell culture and factors influencing the virus yield.
Keywords: Measles virus; Subacute sclerosing panencephalitis; Major complement protein; Cytopathic effect